Flores Augustini : Augustinian florilegia in the Middle Ages - Delmulle, Jérémy; Partoens, Gert; Boodts, Shari; Dupont, Anthony (Spicilegium sacrum Lovaniense, 2020)
"Augustine of Hippo was one of the first authors to give rise to the need for anthologies devoted to a single author. Today, over a hundred florilegia dedicated solely to Augustine's writings are known. Over the course of the Middle Ages, several of these collections proved instrumental in giving access to the Bishop of Hippo's large oeuvre, and in determining the direction of its reception. In fourteen chapters, this volume presents some important Augustinian florilegia, their sources, composition, context, afterlife, and the challenges inherent in editing and studying them. Beginning in Late Antiquity, with Vincent of Lérins and Prosper of Aquitaine, the volume discusses several medieval and early modern florilegia, both well-known and more marginal, and concludes with their use by Augustine's modern editors. As such, this book contributes to a better understanding of the reception of Augustine throughout the Middle Ages and to the ways in which his exceptional auctoritas took shape." --provided by publisher, back cover
Keywords: Augustine, : Saint, Bishop of Hippo : Written works; Augustine, : of Hippo, Saint, : 354-430 : Literary collections; Anthologies